Potato Virus Y and Shallot Latent Virus of Kajoran Horticultural Production Center, Magelang Regency, Indonesia: Molecular Characterization Case Study - Adyatma Irawan Santosa; Adenisa Hanifah Irbati; Krisnanda Surya Dharma; Belinda Winona; Reko Saputra Jaya; Annisa Lisa Andriyani; Chilya Qurrota A'yun (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Kajoran Sub-district is a horticultural production center that supplies horticultural commodities for Central Java Province, especially Magelang. However, plant viral diseases of Kajoran have not been studied. This paper aimed to identify plant viral diseases in this horticultural production center. Some samples were taken: three potatoes (Solanum tuberosum) and three shallots (Allium cepa var. aggregatum), then tested respectively with RT-PCR, using two pairs of universal primers to detect Potyvirus and Carlavirus. The result showed two potato samples were infected by Potyvirus (potato virus Y/PVY) and three shallot samples by Carlavirus (shallot latent virus/SLV). GenBank accession no. OR180052 to OR180056 were assigned to the obtained partial sequences of the five isolates. The phylogenetic analysis makes the two new PVY Indonesian isolates in strain N group thus confirmed the presence of the first PVYN in Indonesia. The constructed SLV phylogenetic tree clusters the new three isolates with eight shallot isolates in a group and separated it from isolates from other plant species. The tested PVY isolates shared 95.2 to 100% nucleotide identities among them, while 78.9 to 98.5% identities were estimated among compared SLV isolates. This study expands our understanding of the genetic variation of PVY and SLV in Indonesia, potentially leading us to find the perfect management for the viruses.